A study on the allylic oxidation of some β-rose ketones - Deshou Mao; Shihua Zhu; Yafen Zhao; Wenwen Zhang; Ruilin Hu; Bingbiao Cai; Cenming Zhu; Ankun Zhou; Jianfeng Li (Results in Chemistry)
A study on the allylic oxidation of β-rose ketones was conducted. The oxo-derivatives of three representative rose ketones β-damascone, β-damascenone and β-ionone were synthesized by using Rh-catalyzed allylic oxidation in good yields at room temperature in the presence of tert-butyl hydroperoxide. Some typical oxidants for allylic oxidation were screened to compare with the Rh-catalyzed reaction by using HPLC analysis (external standard method). The conventional oxidants, i.e. CrO3 and SeO2 with different modified conditions gave generally inferior yields. These results indicated that this method exhibited high efficiency and good selectivity in the oxidation of β-rose ketones. The presence of water played an important role in promoting the oxidation reaction. The Rh-catalyzed reactions can be conducted under mild, environment friendly reaction conditions, very low loading of catalyst and the possibility of repeated use of Rh-catalyst, making it a competitive method for large scale preparations of such fragrances.